Challenges in the global cereal supply chain - Ibba, Maria Itria; Timsina, Jagadish; Odjo, Sylvanus; Palacios-Rojas, Natalia; Pawan Kumar Singh; Xinyao He; Alakonya, Amos; Krupnik, Timothy J.; Sonder, Kai (Elsevier, 2025)
Corn, wheat, and rice are the world’s most widely grown and sizably consumed staple foods. Despite increased interest and the need and willingness to diversify diets, these crops continue to provide an estimated 42% of the world’s food calories and 37% of protein intake (Collete et al., 2014; FAOSTAT, 2023). Their grains are used in popular daily foods and have relatively long shelf lives. Their yields per area sown surpass those of other crops, and they are part of human culture, traditions, economies, and politics. With the world population projected to reach about 9.3 billion by 2050, the demand for these crops is expected to increase significantly, especially in developing regions including Africa and Asia, which are anticipated to have the fastest population growth (OECD/FAO, 2021; UN DESA/POP/2022/TR/ NO, 2022). Feeding a larger population will require not only dramatic increases in corn, wheat, and rice production but also more efficient ways to minimize grain losses during production, storage, and trade. At the same time, the effects of climate change, pandemics, market instabilities, and conflicts disrupt cereal-based agricultural systems and related supply chains, and these are expected to intensify, pushing an additional 75e95 million people into extreme poverty (United Nations, 2022). This chapter describes specific challenges to corn, wheat, and rice farming and supply chains worldwide, considering the complexity of constraint scenarios and the effects of cases such as the COVID-19 pandemic and the Ukraine-Russia war. In this context, this chapter covers grain safety during production, storage, and transportation and the roles of plant breeding, integrated pest management, and agronomy in future supplies of these cereals.